Valuasi Ekonomi Hutan Mangrove (Studi pada Kawasan Pesisir Laut Utara Pulau Jawa) - Herman Cahyo Diartho; Agus Luthfi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
In the mangrove forest ecosystem in the Java Island Coastal Area, there are shrimp and fish ponds owned by the community. Mangrove formations in coastal areas are generally the same, which is Avicennia spp, and are found from the boundaries of residential villages to far ahead of pond areas, specifically on aanslibbing which is the result of sedimentation from the coast and deposition from the sea. The Total Economic Value of mangrove ecosystems in the coastal area of Kraton District, Pasuruan Regency is the sum of benefit values, such as Direct Use Value, Indirect Use Value, Option Value, and Existence Value.The results of this study explained that the indirect benefits of mangrove forest ecosystems in Kraton District, Pasuruan Regency have the largest percentage which is 90.74% with a value of Rp. 4,807,905,315.53/year. The value of the greatest indirect benefits explains the ecological benefits of mangrove forests which are the greatest compared to economic and social benefits. Meanwhile, direct benefits are the second largest with a value of Rp. 185,145,655.00. This considerable value is due to the large value of the benefits of other biotas around the mangrove ecosystem. The total value of these direct benefits directly provides an indicator of economic benefits. The same result was also obtained from research conducted by Rangkuti (2013) where mangrove cover significantly contributed to daily shrimp and crab/biota catches (99% confidence interval). Furthermore, other benefits were identified, such as the benefits of choice and the benefits of existence. The results of the quantification of other benefits obtained successively the value of the optional benefit of Rp. 16,440,975.00/year (3.97%) and the value of the existence benefit of Rp. 20,782,079.29/year (0.52%). The comparison of the benefits generated from the mangrove forest ecosystem further strengthens that the ecological value of the mangrove forest is the greatest. Therefore, the community should be aware of the importance of managing the mangrove ecosystem while maintaining its sustainability. This means that the change in the mangrove forest ecosystem by becoming a shrimp pond system will be ecologically resistant and the real impact is the damage to the coastal environment which is no longer a barrier from waves crashing on the edge of the mainland.